Reliability of research data obtained by grounded theory methodology - Božić, Jasmina (2010)
The paper analyses evaluation procedures of reliability of data obtained by grounded theory research in sociology. Similarly to some other qualitative research methods, reliability, viz. replicability or consistency in grounded theory refers to complementarity of findings of different researchers on the same object. In other words, with an identical theoretical perspective, and through following prescribed data collection and analysis procedures, general concepts reached should be comparable. In order to enable that, the research process should be clearly described. We discuss elements of the research report that are necessary for data reliability assessement. Further, we have undertaken comparative analysis of several grounded theory research studies, including those of grounded theory founders, as well as own doctoral thesis (Božić, J.: How university teachers of the Faculty of Humanities and Social Sciences in Zagreb understand the Bologna process?: The theory of local discourse of Bologna process generated by grounded theory methodology) with a view to validating the research process and grounding of results, that is, supstantive theories generated, through criteria applicable to assessment of grounded theory research results.